Harry Potter and the Chamber of Secrets : 2/7 (Harry Potter 2) - Rowling, J.K. (London Bloomsbury Publishing Ltd, 2014)
Harry Potter's summer has included the worst birthday ever, doomy warnings from a house-elf called Dobby, and rescue from the Dursleys by his friend Ron Weasley in a magical flying car! Back at Hogwarts School of Witchcraft and Wizardry for his second year, Harry hears strange whispers echo through empty corridors - and then the attacks start. Students are found as though turned to stone . Dobby's sinister predictions seem to be coming true. These new editions of the classic and internationally bestselling, multi-award-winning series feature instantly pick-up-able new jackets by Jonny Duddle, with huge child appeal, to bring Harry Potter to the next generation of readers. It's time to PASS THE MAGIC ON .